MAKNA SIMBOL ADAT MBEMBENG DAN NENUROU PADA ETNIS MELAYU ENIM - Virgiana, Bianca; Margareta, Trisia (Jurnal Publisitas, 2019)
Communication is related to the cultures because they need communication, and there are symbols in communication that should be learnt, one of them is the custom marriage of Lubuk Nipis society Tanjung Agung districts, Muara Enim regency. There is a series of nonverbal communication in the application of Lubuk Nipis customary community procession that has symbolic meaning, namely Mbembeng and Nenurou. The aimed of this research was to find out the meaning of the message in Mbembeng and Nenurou tradition on the procession of customary marriage in Lubuk Nipis. The approach used in this research was Symbolic Interactionism Theory. It depends on the individual in constructing the meaning by interacting and communicating. The method of this research was descriptive qualitative by applying depth interview to the key informant. The result was the meaning of customary marriage of Mbembeng and Nenurou were expression of gratitude of a family to the society because of their cooperation, pray for the bride’s life to always be happy and wading the ark together. In addition, there are four steps in the customary marriage of Lubuk Nipis. Lubuk Nipis society belief the Mbembeng and Nenurou had a ritual and sacred meaning on it.